Evaluation of the Implementation of the Family Hope Program (PKH) in Improving the Welfare of Beneficiary Families in Undrusbinangun Village - Ima Muhimah; Kinanti Dinda Azzahra; Muhamad Rafli; Nauvira Elma Elrica; Rahmawati Dwi Lestari; Wahyu Nugroho; Stefani (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the Implementation of the Family Hope Program (PKH) in Undrusbinangun Village, Kadudampit District, Sukabumi Regency, whether the implementation of PKH so far has been in accordance with the indicators of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy of PKH beneficiaries. This research was conducted in Undrusbinangun Village, Kadudampit District, Sukabumi Regency. This study used a qualitative approach with descriptive research as the type of research used. Data collection techniques were carried out by means of field surveys, open interviews, and literature studies, as well as through data provided by related parties. The resource persons for this study were the Chairperson of the PKH Kempok Undrusbinangun Hamlet, the PKH Coordinator and the Beneficiary Families (KPM). The results of this study indicate that the use of existing resources in managing PKH in Undrusbinangun Village, Kadudampit District has been running quite efficiently, this is evidenced by the few resources used in managing PKH but this does not necessarily make PKH management a mess. , but precisely with these resources the PKH program in this village has been running quite well and consistently since 2019.